Sulphonamidic Groups as Electron-Withdrawing Units in Ureido-Based Anion Receptors: Enhanced Anion Complexation versus Deprotonation - Salvadori, Karolína; Šimková, Ludmila; Císařová, Ivana; Sýkora, Jan; Ludvík, Jiří; Cuřínová, Petra (ChemPlusChem, 2020)
A sulphonamidic moiety was utilized as an electron-withdrawing group for enhancement of anion complexation features of urea-based receptors. A series of receptors varying in acidity of sulphonamidic and urea NH groups was synthesized and thoroughly tested. The individual complexation properties reflect deprotonation/complexation equilibrium in a given molecule as a function of the substitution. The receptors containing electron-donating groups in conjugation to the sulphonamidic moiety showed higher association constants towards H2 PO4- and carboxylate anions, while those containing electron-withdrawing groups inclined to deprotonation of sulphonamidic NH. The deprotonation issue can be avoided by alkylation at the early step of receptor synthesis or it can be utilized for insertion of suitable groups that enable its anchoring on various substrates to form more elaborated receptor structures.
Keywords: alkylace; urea-based receptors; electron-withdrawing groups; kyseliny fosforečné; Alkylation; Electrons; Phosphoric Acids; Proton Magnetic Resonance Spectroscopy; Spectrophotometry, Ultraviolet; anion recognition; host-guest systems; sulfonamidy; Anions; protonová magnetická rezonanční spektroskopie; anionty; Sulfonamides; močovina; Protons; elektrony; spektrofotometrie ultrafialová; sulphonamides; Urea; protony